The need to pay attention to differences in health literacy and knowledge in health education interventions - Rahman Panahi; Nahid Aghaeian; Maliheh Pishvaei; Shamsaddin Niknami (Gonabad University of Medical Sciences, 2019)
The Health Literacy (HL) is an individual and social capacity for access, understanding, evaluation of information and health services, and optimal utilization of it for health promotion [1]. Today, HL has been recognized as an important and vital indicator of the results and costs of health care the need for the effective health care system, has a good level of health literacy [2]. According to studies by the United States Health Care Strategies, people with low levels of HL are less likely to understand the written and spoken information provided by health professionals and act according to instructions, and therefore the have a poorer health status, hospitalization rates and referrals to the doctor are higher, they act poorly in self-care skills, have less preventive care, and thus incur more medical expenses [1].